Innovative Learning Paths in Biology Education: Integrating Educational Technology and Transdisciplinary Approaches in the Era of Industry 5.0 - Sari, Winda Purnama; Wardani, Erika Fitri (The Indonesian Institute of Science and Technology Research, 2025)
This study explores the transformation of biology learning paths through the integration of educational technologies and transdisciplinary strategies within the context of Industry 5.0 and Society 5.0. Using qualitative and design-based methods, we developed learning frameworks incorporating both hard and soft technologies, including AI applications, big data, virtual labs, and STEAM-based projects. Results show that educational innovations not only enrich students' conceptual understanding but also cultivate 21st-century competencies such as analytical thinking, collaboration, and problem-solving. The study proposes a dynamic instructional model aligned with real-world issues and concludes that adaptive ecosystems in educational institutions are essential for preparing responsible and innovative future scientists.